Conversor Flyback bidirecional multi enrolamentos - Campos, Arceu Santos Cordeiro de (2018)
DC Micro/nanogrids have become the subject of much attention recently due to the increasing interest in operation of renewable energy sources and electric vehicles in the utility grid. A multi-bus hybrid microgrid has the potential to supply different loads with different voltage levels. This work shows a new topology of the bi-directional Flyback converter with multiple windings, that can be used in microgrid DC systems. The proposed converter topology can interconnect several DC voltage buses allowing the power flow through several buses. The control technique allows soft switch and power transfer between the buses depending on demand. This work has been presented the operating stages and simulation results for a four windings bidirectional Flyback converter.